A Randomized Controlled Trial with a Medical Device Containing Sodium Hyaluronate and Nicotinic Acid to Increase the Efficacy of Ultraviolet Phototherapy in Psoriasis - Balázs Bende; Róbert Kui; Annamária Németh; Mariann Borsos; Zoltán Tóbiás; Gábor Erős; Lajos Kemény; Eszter Baltás (Adis, Springer Healthcare, 2020)
Abstract Introduction The dry and scaly skin of psoriatic patients decreases the efficacy of ultraviolet B (UVB) phototherapy. Different agents are used to facilitate the transmission of light, but most of these preparations are cosmetically unfavorable. We have tested a novel preparation containing sodium hyaluronate and nicotinic acid (UV Fotogel®; Pernix Ltd.) with the double aim to improve the efficacy of UVB phototherapy and assess the cosmetic acceptability of the preparation. Methods Ninety patients with plaque psoriasis were enrolled in the study, of whom 44 received narrow-band UVB (NB-UVB) phototherapy. Prior to phototherapy, one side of the patient's body was treated with UV Fotogel while the other side served as a control. The other 46 patients used the preparation at their homes before regular sunbathing. The Local Psoriasis Severity Index (L-PSI), cosmetic acceptability and tolerability were recorded. The median values with the 25th and 75th percentiles (25p and 75p, respectively) were determined for the UV Fotogel-treated and control sites and then compared. Results The sides of the body to which UV Fotogel was applied prior to NB-UVB phototherapy had a significantly lower median L-PSI score than the non-treated control sides at the end of the treatment (1.0 [25p-75p: 0.0-2.0] vs. 2.0 [1.0-3.0], respectively). The application of UV Fotogel prior to sunbathing also led to a significant decrease in L-PSI score. There was a significant reduction in the median L-PSI score of patients at the final visit compared to baseline (2.5 [25p-75p: 1.5-3.5] vs. 6.0 [6.0-7.0], respectively). Use of the preparation was not accompanied by considerable adverse effects, and the patients found it cosmetically acceptable. Application of UV Fotogel prior to sunbathing was well tolerated by the patients, and the cosmetic acceptability was also good. Conclusion UV Fotogel is potentially a useful device for enhancement of the efficacy of phototherapy in patients with psoriasis.